IDENTIFIKASI TANTANGAN YANG DIHADAPI GURU DALAM IMPLEMENTASI PENDIDIKAN INKLUSIF DI SEKOLAH DASAR NEGERI 1 GEMEL DAN SEKOLAH DASAR NEGERI BATUTULIS - Yuraeda Mufidah; Lalu Hamdian Affandi; Ida Ermiana (Renjana Pendidikan Dasar, 2021)
This research aims to describe the challenges faced by teachers in implementing the learning assessments in inclusive class at SDN I Gemel and SDN Batutulis. This research used a qualitative approach with Narrative Inquiry as a type of research. The data collection techniques were collected from interviews, observation guidelines, and documentation. This research used Milles and Huberman’s theory in analyzing the data. The results showed that the challenges faced by teachers included challenges that related to students, challenges related to teachers, and challenges related to the instrument and learning assessment techniques. Some of these challenges were influenced by several factors, such as 1. Initial identification factors. 2. Teacher competency factors. 3. Curriculum factors. 4. Facility and infrastructure factors. 5. Parents factors. 6. Internal factors or personality of students with special needs. It can be concluded that teachers at SDN I Gemel and SDN Batutulis faced some challenges in implementing learning assessments in inclusive class due to several factors. The teachers had some strategies in facing these challenges, such as 1. Involving regular students as volunteers for helping special needs students. 2. Modifying the instrument and evaluation techniques 3. Study groups. 4. Identifying special needs students regularly. 5. Flexibility of time. 6. Upgrading the teacher’s ability in implementing the assessments of special needs students in the inclusive class.